Touch detection of neonatal hypothermia in Nepal - Ellis, M (BMJ Group, 2006)
The use of touch by health workers to detect hypothermia was examined in 250 newborns in Nepal. Palpation of the feet shows fair interobserver agreement (κ  =  0.4–0.7) and high sensitivity (>80%) but low specificity (36%–74%) compared with axillary thermometry. Traditional birth attendants should feel an infant's feet to detect hypothermia.